2015
DOI: 10.1007/s11852-015-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Salinization during salt-marsh restoration after managed realignment

Abstract: Salt marshes provide an important and unique habitat for plants and animals. To restore salt marshes, numerous coastal realignment projects have been carried out, but restored marshes often show persistent ecological differences from natural marshes. We evaluate the effects of elevation and marsh topography, which are in turn affected by drainage and livestock grazing, on soil salinity after de-embankment. Salinity in the topsoil was monitored during the first 10 years after de-embankment and compared with sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Indeed, ungrazed sites in our study area have been shown to develop significantly higher elevation and lower salinity than grazed sites (Veeneklaas et al. ), which is linked to both sediment accretion and compaction processes (Esselink et al. ).…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, ungrazed sites in our study area have been shown to develop significantly higher elevation and lower salinity than grazed sites (Veeneklaas et al. ), which is linked to both sediment accretion and compaction processes (Esselink et al. ).…”
Section: Discussionmentioning
confidence: 71%
“…Since there were three breaches and three creeks, we had three stations for each station class. In order to assess the effect of livestock grazing on SEC in the restored site, at each station, an exclosure (9 m × 27 m) was established before the start of the first grazing season after deembankment (Veeneklaas et al 2015). An exclosure is a small area permanently protected against grazing.…”
Section: Sec Measurementsmentioning
confidence: 99%
“…Colonisation therefore also depends on suitable environmental conditions for the species to germinate and establish (Morzaria‐Luna & Zedler, 2007; Wolters et al ., 2008). For salt marsh species environmental conditions such as salinity, flooding frequency and duration determine establishment success (Veenklaas et al ., 2015; Edge et al ., 2019). The combination of environmental conditions and competitive abilities of species leads to a distinct zonation of vegetation along elevational gradients in European salt marshes (Petersen et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%